Two circular cylinders in cross-flow: A review - Sumner, D. (Journal of fluids and structures, 2010)
Pairs of circular cylinders immersed in a steady cross-flow are encountered in many engineering applications. The cylinders may be arranged in tandem, side-by-side, or staggered configurations. Wake and proximity interference effects, which are determined primarily by the longitudinal and transverse spacing between the cylinders, and also by the Reynolds number, have a strong influence on the flow patterns, aerodynamic forces, vortex shedding, and other parameters. This paper reviews the current understanding of the flow around two “infinite” circular cylinders of equal diameter immersed in a steady cross-flow, with a focus on the near-wake flow patterns, Reynolds number effects, intermediate wake structure and behaviour, and the general trends in the measurements of the aerodynamic force coefficients and Strouhal numbers. A primary focus is on the key experimental and numerical studies that have appeared since the last major review of this subject more than 20 years ago.